1997
DOI: 10.1103/physrevb.55.5611
|View full text |Cite
|
Sign up to set email alerts
|

Nonextensivity and Tsallis statistics in magnetic systems

Abstract: We have studied the role of long-range interactions on the thermodynamics of magnetic systems. We have simulated, through the Monte Carlo method, magnetization curves of a two-dimensional classical Ising model including a long-range dipole-dipole-like interaction, where the range of interaction is tuned by a parameter ␣. Based on the conjectures of Tsallis statistics, we show that, for ␣/dр1 (dϭ2), the appropriate form of the equation of state is given by M /Nϭm(T*,H*) with T*ϵT/N* and H*ϵH/N*. The normalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 19 publications
5
35
0
Order By: Relevance
“…The case of long-range interactions is more subtle. This case is conveniently discussed by introducing a variable such as the following one [34,35,36,37,38,39,40,41,42,43,44]:…”
Section: Generalizing Thermodynamicsmentioning
confidence: 99%
“…The case of long-range interactions is more subtle. This case is conveniently discussed by introducing a variable such as the following one [34,35,36,37,38,39,40,41,42,43,44]:…”
Section: Generalizing Thermodynamicsmentioning
confidence: 99%
“…A first result was to obtain the scaling laws that follow from the application of Boltzmann-Gibbs statistics to a genuinely non-extensive system such as the LRIM in the regime α < d. The results for the internal energy, U, the magnetization M (defined as M = | N i=1 s i | and computed using Eq. (23)), the Helmholtz free energy F and the entropy S can be summarized by the following relations [26,27,18,[28][29][30]:…”
Section: The Scaling Functionsmentioning
confidence: 99%
“…4 ͑3͒ suggested by Tsallis 28 and later observed in Monte Carlo simulations. 26 Although field scaling gives rise to a significantly improved data collapse for m A / m B vs H and m A / m C vs H ͓Fig. 4͑a͒-4͑e͔͒, there is no significant improvement when considering m B / m C vs H ͓Fig.…”
Section: Instead Of Using the Resultsmentioning
confidence: 99%
“…From Eq. ͑1͒, it can be concluded that renormalization of U / N allows one to recover convergence according to U / ͑N ln N͒ → const for N → ϱ. Tsallis extended this reasoning to the Gibbs free energy, G. For a 3D system with dipolar interactions, Tsallis's scaling approach reads 26,28 …”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation